Vegetable biocholine supplementation in pre- and postpartum Lacaune sheep: Effects on animal health, milk production and quality - Alba D.F.* (2020)
© 2020 Elsevier B.V.In the final third of gestation and during early lactation, sheep require a large supply of nutrients to support fetal growth, mammary gland development, and milk production. Nevertheless, during this period, the pregnant ewe consumes less feed in the context of increased energy expenditure and hepatic overload. For these reasons, natural products have been used as supplements to minimize the negative effects of this transition phase. The objective of the present study was to determine whether supplementation with vegetable biocholine (VB) in pregnant and lactating sheep (transition period) would improve milk production and quality and overall health. The experiment lasted 65 days, corresponding to the final 20 days of pregnancy and the first 45 days of lactation. A total of 24 Lacaune ewes [2.30 ± 0.56 L of milk/day at 15 days postpartum (average production in previous lactation)] were separated into two homogeneous groups on day 20 prenatally: a control group (without supplementation) and a treated group in which the animals received 5 g of VB/animal/day. Blood samples were taken on days 20 and 10 before delivery, the day of delivery and on days 7, 15, 30 and 45 after delivery. Measurements of milk yield, as well as milk collections for composition analysis (fat, protein, lactose and total solids) were performed on the 15th, 30th and 45th postpartum days. The sheep that consumed VB in the diet had higher lactation persistence than did control (P < 0.05), and tended to have greater (P = 0.10) milk production (Control = 1.94 L/day; Treated = 2.23 L/day). Milk composition did not differ significantly between the groups at the three time points (P>0.05). We observed greater activity of glutathione S-transferase (GST) and glutathione peroxidase (GPx) in milk (P <0.05); there was also a tendency toward lower somatic cell counts in the milk of the sheep in the treated group on day 45 (P = 0.07). Higher activities of GPx and GST also were observed in the serum the treated group (P < 0.05). At 45 days postpartum, sheep in the treated group had lower liver enzyme activities (aspartate aminotransferase and gamma glutamyltransferase) (P <0.05), and lower albumin levels at days 15 and 30 (P <0.05). Globulin levels were greater in serum of VB-supplemented sheep than in controls (P <0.05). Vegetable biocholine intake by sheep reduced serum calcium levels (P <0.05). We conclude that the addition of VB in the diet of sheep improved health and milk quality but did not affect milk composition though it tended to increase milk production.